The Moscow Offensive - Brown, Dale, 1956- (New York, NY : William Morrow, an imprint of HarperCollins Publishers, 2018)
"Americas first line of defense--Brad McLanahan and the heroes of the Iron Wolf Squadron--must counter a dangerous Russian strike from within the homeland. On a remote island estate, a billionaire investor sells his air freight company to a mysterious new owner. The purchaser is none other than the President of Russia, Gennadiy Gryzlov. The Russians will use these private planes to secretly transport dangerous cargo into the United States. The inept American President Stacy Anne Barbeau has failed to account for the Russian threat. But others have been vigilant and will not leave America defenseless."--
"A novel"--cover.
Keywords: Special operations (Military science) -- Fiction; Special forces (Military science) -- Fiction; Terrorism -- Prevention; Fiction; Suspense fiction